The Effect of Probiotic Yogurt and Fermented Skim Milk Beverages on The Reduction of Streptococcus Mutans In Children's Dental Caries - Eko Sri Yuni Astuti; Putu Ariska Indraswari; Putu Widani Astuti; Yudha Rahina (Interdental Jurnal Kedokteran Gigi (IJKG), 2024)
Introduction: Dental caries is the most common dental and oral problem in children, with a prevalence of 90.2% in children under 6 years old . Streptococcus mutans is considered one of the most virulent caries-causing microorganisms due to its ability to colonize and initiate plaque formation on tooth surfaces. Probiotic yogurt and skim milk-based fermented drinks, which are popular with children, can potentially inhibit the growth of pathogenic oral bacteria. This study aimed to determine the effect of these probiotic drinks on reducing Streptococcus mutans counts in pediatric dental caries. Materials and Methods: This in vitro laboratory study used a post-test only control group design. Streptococcus mutans colonies obtained from human dental plaque were immersed in artificial saliva with yogurt for 4 minutes, skim milk-based fermented drinks for 2 minutes, or distilled water (negative control) for 2 or 4 minutes. Bacterial growth was observed and analyzed statistically. Results: Both probiotic yogurt drinks and skim milk-based fermented drinks reduced the number of Streptococcus mutans bacteria. Conclusion: Skim milk-based fermented beverages showed a greater reduction in Streptococcus mutans compared to yogurt. Poor oral hygiene practices, cariogenic diets, and low socioeconomic status are reported risk factors for dental caries in children. Regular tooth brushing and limiting sugar consumption can help prevent caries development.